2001
DOI: 10.1007/bf02967492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone metabolic markers in breast cancer with bone metastasis

Abstract: We confirmed that ICTP and TRACP might be useful markers for screening and monitoring BM in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 20 publications
3
32
0
3
Order By: Relevance
“…Levels of TRAP activity in the serum in this study were about 1/6 of that in previous studies on healthy adult humans [1,21,24,26], and serum TRAP activity was significantly correlated with the serum hydroxyproline concentration. From these results, TRAP activity is a useful index of bone resorption even though the activities were low.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Levels of TRAP activity in the serum in this study were about 1/6 of that in previous studies on healthy adult humans [1,21,24,26], and serum TRAP activity was significantly correlated with the serum hydroxyproline concentration. From these results, TRAP activity is a useful index of bone resorption even though the activities were low.…”
supporting
confidence: 59%
“…TRAP activity in serum has been utilized as a bone resorption marker for diagnosis and monitoring of the effectiveness of treatment of metabolic bone disorders in humans [1,21,24,26]. Lau et al isolated TRAP from bovine bone matrix, and reported that it resembled human TRAP originating from osteoclasts in biological character [13].…”
mentioning
confidence: 99%
“…The authors speculated that this elevation may reflect subclinical bone involvement. Wada et al 63 retrospectively analyzed four bone markers (NTX-I, ICTP, total ALP and TRAP5b) in 156 breast cancer patients, 23 with bone-only metastases, 19 with extraosseous-only metastases and 114 without metastases. Those with BM were further divided by the number of bone lesions.…”
Section: Diagnosis Of Bone Metastasesmentioning
confidence: 99%
“…Patients with advanced cancer and bone metastases typically have elevated levels of the bone turnover markers (BTM) urinary N-telopeptide (uNTx), an indicator of osteoclast activity, and serum bone-specific alkaline phosphatase (sBSAP), an indicator of osteoblast activity (6,7,(30)(31)(32). Both denosumab and zoledronic acid have been shown to significantly reduce uNTx and sBSAP levels (33,34), and these two BTMs have been investigated as potential prognostic factors for monitoring patients with cancer who are receiving bone antiresorptive agents.…”
Section: Introductionmentioning
confidence: 99%